Harmony through melody : the interaction of melody, counterpoint, and harmony in Western music /: the interaction of melody, counterpoint, and harmony in Western music. (2020) - Horton, Charles, 1952-; Byrne, David A, 1970-; Ritchey, Lawrence
No abstract available